A method of strengthening monitored deficient bridges - Decker, Brandon Richard (Kansas State University, 2007)
There is a high need to repair or replace many bridges in the state of Kansas. 23% of the bridges in Kansas are labeled structurally deficient or functionally obsolete. A majority of these bridges serve rural areas and are damaged due to overloading during harvest season. A state-of-the-art method of performing structural health monitoring on these bridges followed by an effective method of strengthening and repair was researched and presented in this thesis. The first phase of this research involved researching multiple devices to be used for state-of-the-art health monitoring. After deciding on an appropriate system, multiple tests were performed to determine the systems performance compared against conventional systems. The system was tested on a laboratory scale pre-stressed concrete T-beam. The system was tested on its ability to effectively record and transmit acceleration data. If this system were to be implemented on an actual bridge, KDOT could make a decision to repair or strengthen the bridge based on the results. The next phase of the research was to determine an effective strengthening procedure using carbon fiber reinforced polymer (CFRP). Reinforced concrete beam specimens were cast and tested in the lab. The specimens consisted of rectangular and T-shaped cross-sections to create different failure modes when tested in bending. The primary issue when strengthening with CFRP is the issue of early separation failure when using CFRP in the longitudinal direction only. In an effort to prove this, the specimens were strengthened with five layers of CFRP and tested in four-point bending until failure. In an effort to prevent early separation failure, CFRP “U-wraps” were applied to provide shear resistance and additional anchorage for the flexural CFRP. The beams were then tested in flexure until failure by FRP rupture or concrete crushing followed by FRP rupture. The test results indicate that the U-wraps allowed the FRP to reach full capacity and fail in FRP rupture. The use of CFRP provided a strength increase of about 220% over the control beam specimens while significantly reducing the ultimate deflection.
Keywords: CFRP; wireless; strengthening; monitoring; Engineering, Civil (0543)